1998
DOI: 10.1590/s0100-879x1998001000017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Walker 256 tumor growth on intestinal absorption of leucine, methionine and glucose in newly weaned and mature rats

Abstract: In tumor-bearing rats, most of the serum amino acids are used for synthesis and oxidation processes by the neoplastic tissue. In the present study, the effect of Walker 256 carcinoma growth on the intestinal absorption of leucine, methionine and glucose was investigated in newly weaned and mature rats. Food intake and carcass weight were decreased in newly weaned (NT) and mature (MT) rats bearing Walker 256 tumor in comparison with control animals (NC and MC). The tumor/carcass weight ratio was higher in NT th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
8
1
3
Order By: Relevance
“…Although previous studies have showed that there was a reduction on the ratio gut mass/ protein content in groups which were submitted to tumor implant or food restriction decreasing nutrient intestinal absorption [14], in the present study, this ratio can not be related to leucine absorption in pregnant tumor bearing rats. The decrease in glucose intestinal absorption was due to reduction in the food intake; as glucose absorption is up-regulated and depends on its carrier and the pregnant groups (P and L) were adapted to a non-specific regulation of carriers which can be accompanied by mucosal hyperplasia.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Although previous studies have showed that there was a reduction on the ratio gut mass/ protein content in groups which were submitted to tumor implant or food restriction decreasing nutrient intestinal absorption [14], in the present study, this ratio can not be related to leucine absorption in pregnant tumor bearing rats. The decrease in glucose intestinal absorption was due to reduction in the food intake; as glucose absorption is up-regulated and depends on its carrier and the pregnant groups (P and L) were adapted to a non-specific regulation of carriers which can be accompanied by mucosal hyperplasia.…”
Section: Discussioncontrasting
confidence: 77%
“…Increased glucagon levels can lead to anorexia, as well as increased hepatic gluconeogenesis and utilisation of gluconeogenic amino acids at the expense of protein synthesis, leading to a negative energy balance [25]. In a recent study, decrease on food intake was observed in Walker tumor -bearing rats associated to highly decrease in carcass weight [13,14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumour‐bearing rats received a subcutaneous injection of approximately 2.5 × 10 6 Walker‐256 carcinoma cells in a 0.9% NaCl suspension (0.5 mL) in the right flank . The rats without tumours received a unique injection containing a 0.5 mL NaCl solution (0.9% w/v ) without anaesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…A decrease in this parameter represents a decrease in the efficiency of energy intake, one of the key components of the energy balance. In cancer, lipid and carbohydrate alterations in intestinal absorption have been reported in both humans [6] and experimental animals [7,8]. Malabsorption is generally attributed to the consequences of oncologic treatments reducing the gastrointestinal absorption.…”
Section: Altered Intestinal Absorption Of Nutrientsmentioning
confidence: 99%